2022
DOI: 10.1101/2022.09.05.506663
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An Alpha-helical Lid Guides the Target DNA toward Catalysis in CRISPR-Cas12a

Abstract: CRISPR-Cas12a is a powerful RNA-guided genome-editing system, also emerging as a robust diagnostic tool that cleaves double-stranded DNA using only the RuvC domain. This opens an overarching question on how the spatially distant DNA target strand (TS) traverses toward the RuvC catalytic core. Here, continuous tens of microsecond-long molecular dynamics and free- energy simulations reveal that an ⍺-helical lid, located within the RuvC domain, plays a pivotal role in the traversal of the TS by anchoring the crRN… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…3 and 4). A number of studies have revealed DNA conformational changes post NTS-nicking in Cas12a (24,30,31,45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 and 4). A number of studies have revealed DNA conformational changes post NTS-nicking in Cas12a (24,30,31,45).…”
Section: Discussionmentioning
confidence: 99%
“…While Cas9 cleaves a DNA target using two nuclease domains in a parallel-sequential fashion (27)(28)(29), Cas12a causes double-stranded DNA breaks using a single RuvC nuclease domain following a sequential mechanism, with the NTS being cleaved first at a site located in the PAM-distal segment of the protospacer, around 14-18 nucleotides from the PAM (19). Following nicking of the NTS, the protein-RNA-DNA complex undergoes additional conformational changes, eventually enabling cleavage of the TS at a site located 1-2 nucleotides beyond the DNA/RNA hybrid within the R-loop flank (19,30,24,31). Consequently, Cas12a yields a mismatch tolerance pattern that is clearly different from that of Cas9 (32), with little to no tolerance for PAM-distal mismatches (33,34).…”
Section: Introductionmentioning
confidence: 99%
“…158 However, enhanced sampling simulations have recently revealed that an α-helical lid, located within the RuvC domain, also aids in the traversal of the TS by anchoring the crRNA:TS hybrid. 159 ■ BEST PRACTICES TO MODEL PROTEIN/NUCLEIC…”
Section: ■ Gene Editing Systemsmentioning
confidence: 99%
“…Multi-μs MD simulation revealed that DNA binding induces coupled dynamics of the REC2 and RuvC that prime the conformational transition of TS toward the catalytic site . However, enhanced sampling simulations have recently revealed that an α-helical lid, located within the RuvC domain, also aids in the traversal of the TS by anchoring the crRNA:TS hybrid …”
Section: Gene Editing Systemsmentioning
confidence: 99%
“…The role of H983 as a nucleophilic activator is in accordance with mutation data revealing a hampered cleavage of the ntDNA strand when H983 is mutated to alanine. Further in-depth discussion can be found elsewhere ( Nierzwicki et al, 2021 ; Patel and Palermo, 2022 ; SahaAshan et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%